Development of reading skills throughout the waldorf approach in creative thinking abilities in fourth graders of liceo panamericano school during the year 2017-2018 - Alvarez Castañeda, Carlos Magno (2019)
To have a didactic class, the teacher must be a didactic person too. As ympathetic as the previous statement can be, didactic activities can be the same way. Reading gives us the opportunity to expand knowledge and bend it any way possible, giving understanding and significant meaning when didactic activities are applied in the classroom. Didactic classes can be the life of the classroom if they are carried out properly and can stay in a students’ mind all life. That is why the concept of reading can be involved with critical thinking activities as well. They are like a recording device that can help students achieve retention, meaning, inference, problem solving and many other competences….